VEGETACION MARINA DE UN SECTOR DE LA PLATAFORMA CONTINENTAL DE LA GUAJIRA (CARIBE COLOMBIANO) (Boletín de Investigaciones Marinas y Costeras, 2016)
A list of 46 species of marine macrophytes (44 algae and 2 seagrasses) collected between 5 to 36 m depth off Riohacha, on the continental shelf of the peninsula La Guajira (Colombian Caribbean) is presented. 22 species of algae were not previously known from this area. A total of 149 apecies are now registered from the area of La Guajira. Three types of macrophyte asociations were found: (1) dominated by the seagrass Thalassia testudinum with a dry leaf biomass between 27 and 40 gm-2 at 5 m depth. (2) established at -17 m and also dominated by T. testudinum, but with a lower dry leaf biomass (14 gm-2) and a more scattered distribution; green rhizophytic macroalgae (Caulerpa spp.) are quite common. (3) dominated by red and green macroalgae with a total dry biomass of 14 gm-2 at -36 m. 92 % of the species found occurs also in the Santa Marta region, located 160 km far W-SW from the study area. In general, the species found are widely distributed in the Caribbean.